GIANT MAGNETORESISTANCE OBSERVED IN THIN FILM NiFe/Cu/NiFe STRUCTURES - Kisała, Jakub; Kociubiński, Andrzej; Czarnacka, Karolina; Gęca, Mateusz (Informatyka, Automatyka, Pomiary w Gospodarce i Ochronie Środowiska, 2022)
In this paper, the technology for fabricating NiFe/Cu/NiFe layered structures by magnetron sputtering is presented. Two series of samples were fabricated on a glass substrate with a layered structure, where the individual layers were 30 nm NiFe, 5 nm Cu, and finally NiFe with a thickness of 30 nm. The series differed in the type of technology mask used. A constant magnetic field was applied to the substrate during the sputtering of the ferromagnetic layers. Measurements of the DC resistance of the obtained structures in the constant magnetic field of neodymium magnet packs with a constant magnetic field of about 0.5 T magnetic induction have been carried out. Comparison of the two series allows us to conclude the greater validity of using masks in the form of Kapton tape. The obtained results seem to confirm the occurrence of phenomena referred to as the giant magnetoresistance effect.